Predictive validity of the ASAS classification criteria for axial and peripheral spondyloarthritis after follow-up in the ASAS cohort: a final analysis. Issue 6 (10th February 2016) - Sepriano, Alexandre; Landewé, Robert; van der Heijde, Désirée; Sieper, Joachim; Akkoc, Nurullah; Brandt, Jan; Braun, Jürgen; Collantes-Estevez, Eduardo; Dougados, Maxime; Fitzgerald, Oliver; Huang, Feng; Gu, Jieruo; et al.
Abstract : Objective: To establish the predictive validity of the Assessment of SpondyloArthritis international Society (ASAS) spondyloarthritis (SpA) classification criteria. Methods: 22 centres (N=909 patients) from the initial 29 ASAS centres (N=975) participated in the ASAS-cohort follow-up study. Patients had either chronic (>3 months) back pain of unknown origin and age of onset below 45 years (N=658) or peripheral arthritis and/or enthesitis and/or dactylitis (N=251). At follow-up, information was obtained at a clinic visit or by telephone. The positive predictive value (PPV) of the baseline classification by the ASAS criteria was calculated using rheumatologist's diagnosis at follow-up as external standard. Results: In total, 564 patients were assessed at follow-up (345 visits; 219 telephone) with a mean follow-up of 4.4 years (range: 1.9; 6.8) and 70.2% received a SpA diagnosis by the rheumatologist. 335 patients fulfilled the axial SpA (axSpA) or peripheral SpA (pSpA) criteria at baseline and of these, 309 were diagnosed SpA after follow-up (PPV SpA criteria: 92.2%). The PPV of the axSpA and pSpA criteria was 93.3% and 89.5%, respectively. The PPV for the 'clinical arm only' was 88.0% and for the 'clinical arm'±'imaging arm' 96.0%, for the 'imaging arm only' 86.2% and for the 'imaging arm'+/-'clinical arm' 94.7%. A series of sensitivity analyses yielded similar results (range: 85.1–98.2%). Conclusions: The PPV of the axSpA and pSpA criteria to forecast an expert's diagnosis of 'SpA' after more than 4 years is excellent. The 'imaging arm' and 'clinical arm' of the axSpA criteria have similar predictive validity and are truly complementary.